Multi-Institutional Retrospective Study of Radiotherapy for Hepatocellular Carcinoma in the Caudate Lobe - Lee, Sung Uk; Yoon, Sang Min; Cheng, Jason Chia-Hsien; Kim, Tae Hyun; Kim, Bo Hyun; Park, Jin-hong; Jung, Jinhong; Tsai, Chiao-Ling; Chiang, Yun; Park, Joong-Won (Frontiers in Oncology, 2021)
Background: No studies evaluating the clinical outcomes of radiotherapy (RT) for hepatocellular carcinoma (HCC) in the caudate lobe have been available to date. The purpose of this study was to evaluate the effectiveness and safety of RT for HCC in the caudate lobe. Material and Methods: Seventy patients with HCC in the caudate lobe treated with RT from a multi-institutional database were included in this study. The median equivalent dose in 2 Gy (EQD2) was 80.0 Gy10 (range, 31.3 – 99.3), and freedom from local progression (FFLP), progression-free survival (PFS), and overall survival (OS) rates were evaluated. Results: The median time of follow-up was 47.9 months (range, 3.4 – 127), and the 5-year FFLP, PFS, and OS rates were 80.6% (95% confidence interval [CI], 70.8 – 91.8), 13.8% (95% CI, 7.5 – 25.4), and 51.3% (95% CI, 39.9 – 66.1), respectively. In the multivariate analysis, the radiation dose was significantly associated with the FFLP rate (hazard ratio [HR], 0.57 per 10 Gy10 increase, p=0.001), and the status of FFLP was significantly associated with OS (HR, 2.694, p=0.014). The overall rate of ≥grade 3 adverse events was 5.7% (4 of 70), and RT-related mortality was not observed. Conclusion: RT for HCC in the caudate lobe showed promising FFLP and OS rates with safe toxicity profiles. These findings suggest that RT may be a promising treatment option for HCC in the caudate lobe.